Fungal sinusitus: a clinical analysis - Araújo, Elisabeth (2022)
OBJECTIVE: To report the microbiological, histopathological, radiological, and endoscopic findings associated with clinical observations in patients with fungal sinusitis.MATERIALS AND METHODS: A prospective analysis of 829 cases compatible with chronic sinusitis was carried out. Diagnosis of fungal sinusitis was cofirmed in 33patients through computed tomography and nasal endoscopy associated with clinical, laboratorial, microbiological and histopathological findings. These patients were classified as having one of the following: fungus ball sinusitis, alergic fungal sinusitis , acute invasive sinusitus or indolent or slowly invasive sinusitus.RESULTS: 18 patients presented with fungus ball sinusitis, 13 matched the criteria for AFS and two for slowly invasive fungus sinusitis. There were no occurences of fulminant fungal sinusitis. Clinical cure was obtained in 24 patients. Recidivation took place in four alergic fungal sinusitis patients.CONCLUSIONS: Fungal sinusitis presents itself in many different ways and can be treated with a large variety of therapeutical techniques. Therefore it demands not onlya diagnosis of the etiology of the fungus, but also the identification of the sort of sinusitis, through an association of nasal endoscopy, computed tomography, macroscopic examination of the secretion, direct exam, and culture in appropriate medium.